History, Theology, Orthodoxy, Polydoxy. (July 2014) - Burrus, Virginia
Abstract The discourse of orthodoxy and heresy has proven both extraordinarily powerful in its historical effects and woefully inadequate as a historical map of theological diversity. The documents of ancient Christianity reveal subtleties of differentiation that only sometimes come to be framed in polarized terms, as well as violent simplifications of asserted polarities that inevitably hide more than they reveal about a religious movement that placed nearly unprecedented value on both unity and universality even as it thereby also embraced the formidable difficulties entailed by an extreme social, cultural, and theological pluralism. But if historians have failed to take the measure of theological diversity, so too have theologians. Doctrine does not develop in a monolinear fashion, nor is it put on ice in the fourth‐century Mediterranean, or in any other time or place, but is rather the iterative product of the ongoing practice of theologizing—always repeating, always mutating, never finalized, and sprawling across place as well as time. Its elusive truths are conveyed by the testimony of a responsive, generous, and self‐emptying love, as much as by creedal certitude. From this perspective, the recent proposal of Catherine Keller, Laurel Schneider, et al., that the term "polydoxy" displace that of orthodoxy is met with both welcome and wariness. Welcome, as both an affirmation of what has always been and a challenge to live into that heritage more fully. Wariness, if polydoxy should turn out to be just another triumphal orthodoxy, suppressing difference.